Assembly‐Induced Thermogenesis of Gold Nanoparticles in the Presence of Alternating Magnetic Field for Controllable Drug Release of Hydrogel. Issue 48 (13th October 2016) - Wang, Peng; Sun, Jianfei; Lou, Zhichao; Fan, Fengguo; Hu, Ke; Sun, Yi; Gu, Ning
Abstract : Films of gold nanoparticles are easily fabricated by layer‐by‐layer assembly. With increasing number of layers a transition of the electric property from insulating to conducting can be achieved. This conductivity leads to controllable thermogenesis of the film, which can be employed for drug release of loaded hydrogels.